2020
DOI: 10.1007/s00436-019-06591-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and heteroplasmy of Varroa destructor inferred from ND4 mtDNA sequences

Abstract: Varroa destructor, a parasitic mite of the Western honey bee Apis mellifera L., is a serious threat to colonies and beekeeping worldwide. Population genetics of the mite has provided information of two mitochondrial haplotypes infecting honey bee colonies, named K (Korea) and J (Japan). In the American continent, the K haplotype was most frequently found. The aim of this research was to study the genetic diversity of V. destructor populations from the major beekeeping region of Argentina, previously unexplored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…V. jacobsoni 12,7% 10,9% In a related study in Argentina, 100% of mites from six provinces were identified as K haplotype (Maggi et al, 2012), and ten other provinces were recently sampled (Muntaabski et al, 2020). Other studies have also identified related results with more than 95% of mites belonging to K haplotype in Chile (Solignac et al, 2005) and 100% in different areas of Uruguay (Mendoza et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…V. jacobsoni 12,7% 10,9% In a related study in Argentina, 100% of mites from six provinces were identified as K haplotype (Maggi et al, 2012), and ten other provinces were recently sampled (Muntaabski et al, 2020). Other studies have also identified related results with more than 95% of mites belonging to K haplotype in Chile (Solignac et al, 2005) and 100% in different areas of Uruguay (Mendoza et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Other haplotypes exclusively described in Argentina are the K sub-haplotypes KArg-N1 and KArg-N2 that represent polymorphisms of the nd4 gene. Interestingly, of these polymorphisms, heteroplasmic variants including KS1, KP1, and KArg-N1/KArg-N2 have been identified in Serbia and Argentina, respectively [ 66 , 67 , 68 ]. The K haplotype, found in most regions of the world, is by far the most successful in terms of colonization, and has the highest reproductive indices in A. mellifera [ 10 , 60 , 69 ].…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%
“…A second host switching event occurred around 1957, which led to the description of the Japanese haplotype ( Oldroyd 1999 ). While both V. destructor haplotypes have spread west from their countries of origin, the Korean haplotype has become dominant ( Anderson and Trueman 2000 , Guerra Junior et al 2010 , Gajic et al 2013 , Ayan et al 2017 , Kelomey et al 2017 , Octaviano-Salvadé et al 2017 , Hajializadeh et al 2018 , Muntaabski et al 2020 , Ogihara et al 2020 ). Several variants of the Korean and Japanese haplotypes have been identified in parts of Asia ( Navajas et al 2010 ).…”
Section: Varroa Destructor’s Initial Host Switch and Geneticsmentioning
confidence: 99%